2022
DOI: 10.36660/abc.20210931
|View full text |Cite
|
Sign up to set email alerts
|

Impacto da Síndrome Metabólica Relacionada à Infecção por Helicobacter pylori Ativa na Hipertensão Arterial Sistêmica

Abstract: Em sua metanálise, Huang et al., 1 concluíram que a infecção por Helicobacter pylori (infecção por H. pylori) está positivamente associada à hipertensão arterial sistêmica, particularmente pela introdução do teste respiratório diagnóstico de 13C-ureia, significando infecção atual por H. pylori. Correspondência: Jannis Kountouras •

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The pathogenesis of hypertension, a component of MS, mainly involves vascular endothelial dysfunction, sympathetic nerve impairment, and the aberrant activation of the renin-angiotensin-aldosterone system ( Gupta et al, 2022 ). Hypertension is also closely related to HP infection ( Dore et al, 2022 ; Fang, Xie & Fan, 2022 ; Kountouras et al, 2022 ). Yue et al (2022) reported that HP infection increased the risk of hypertension by 32%.…”
Section: Survey Methodologymentioning
confidence: 99%
“…The pathogenesis of hypertension, a component of MS, mainly involves vascular endothelial dysfunction, sympathetic nerve impairment, and the aberrant activation of the renin-angiotensin-aldosterone system ( Gupta et al, 2022 ). Hypertension is also closely related to HP infection ( Dore et al, 2022 ; Fang, Xie & Fan, 2022 ; Kountouras et al, 2022 ). Yue et al (2022) reported that HP infection increased the risk of hypertension by 32%.…”
Section: Survey Methodologymentioning
confidence: 99%
“…Atrial fibrillation (AF) significantly contributes to the morbidity and mortality associated with H. pylori/MetS-related C-CVD [25], especially due to strokes caused by AF, which are similarly related to H. pylori infection/MetS [84]. AF is among the leading causes of stroke related to H. pylori infection and MetS [85].…”
Section: The Role Of H Pylori/mets-related Atrial Fibrillation Pathol...mentioning
confidence: 99%
“…Augmented maternal mortality and low fetal birth weight are observed in patients with AF during pregnancy (Figure 1), with an AF peak at the end of the second trimester [98]. AF causes significant morbidity in women and is typically attributed to cardiac remodeling from various causes, especially AH [99], which is similarly associated with diverse pathologies related to H. pylori infection/MetS [3,25,29]. Obstetric complications are often observed in individuals with AF.…”
Section: The Role Of H Pylori/mets-related Atrial Fibrillation Pathol...mentioning
confidence: 99%
See 2 more Smart Citations